High-radiance phosphor-converted light sources for fluorescence analysis - Müller, Jan; Ramsteiner, Ingo B.; Fieß, Reinhold; Neumann, Cornelius (Advanced Optical Technologies, 2024)
Laser-excited remote phosphor (LERP) light sources have gained significant importance in lighting and display applications due to their unique brightness and color rendering qualities. Beside their known advantages for these applications, we found that they also offer a much less explored potential for sensor applications such as quantitative fluorescence analysis. This applies especially when sophisticated optics under space and cost constraints call for low etendue sources with highly stable spectral properties. In this paper, an example for such an application is given. The purpose of our research is to assess currently available phosphor materials and design a light source for our particular reference application. For this purpose, a characterization setup was set up that compares different phosphors excited by small laser spots with diameters between 100 µm and 280 µm in terms of emitted spectral radiance, incident laser power and irradiance. The investigations identify two suitable phosphors, including a phosphor that closes the gap in the blue and green wavelength range. Furthermore, the importance of small laser spots was demonstrated, which allows to reduce the laser power to simplify light source design and to save costs. The presented research proposes a functional set of phosphors for the above-mentioned application and at the same time presents the current limits of LERP light sources. We remain convinced in the described application field for LERP sources and hope that the needs elaborated in this work will stimulate research and development of novel phosphor materials.